2018
DOI: 10.1080/0886022x.2018.1455596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combination sildenafil and gemfibrozil on cisplatin-induced nephrotoxicity; role of heme oxygenase-1

Abstract: Background/aim: Cisplatin-induced nephrotoxicity in large proportion of patients. The aim of this work is to clarify the effect of combination of sildenafil and gemfibrozil on cisplatin-induced nephrotoxicity either before or after cisplatin treatment and determination of nephrotoxicity predictors among the measured tissue markers.Methods: Thirty two adult male albino rats were divided into four equal groups (G) GI control, GII received cisplatin, GIII received sildenafil and gemfibrozil before cisplatin, GIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…CP administration resulted in an increased level of TNF-α when compared to the control group. This is in agreement with the previous investigations [2830]. Ma et al [11] found that the administration of CP produced a significant increase in TNF-α and IL-6.…”
Section: Discussionsupporting
confidence: 93%
“…CP administration resulted in an increased level of TNF-α when compared to the control group. This is in agreement with the previous investigations [2830]. Ma et al [11] found that the administration of CP produced a significant increase in TNF-α and IL-6.…”
Section: Discussionsupporting
confidence: 93%
“…Vanillin pretreatment prevented CP‐induced kidney damage and preserved kidney function in accordance with previous studies. [ 11,12,30 ]…”
Section: Discussionmentioning
confidence: 99%
“…The forward and reverse primer sequences were as follow: NOX‐4 : forward (5′‐TTCTGGACCTTTGTGCCTATAC‐3′) and reverse (5′‐CCATGACATCTGAGGGATGATT‐3′), [ 26 ] NRF‐2 : forward (5′‐ACGGTGGAGTTCAATGAC‐3′) and reverse (5′‐GAAGAATGTGTTGGCTGTG‐3′), [ 27 ] HO‐1 : forward (5′‐GCCTGCTAGCCTGGTTCAAG‐3′) and reverse (5′‐AGCGGTGTCTGG GATGAACTA‐3′), [ 27 ] GAPDH : forward (5′‐CACCCTGTTGCTGTAGCCATATTC‐3′) and reverse (5′‐GACATCAAGAAGGTGG TGAAGCAG‐3′). [ 12 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with human studies, the Journal has published important works on animal models of AKI as well. These have included work on the potential protective role of N-acetylcysteine in oxalateinduced AKI in a rat model [13], the protective effect of berberine against gentamycin-induced nephrotoxicity in rats [14] and its possible underlying mechanisms, and explored the protective role of heme oxygenase-1 on the course of cisplatin-induced nephrotoxicity [15].…”
Section: Greetings To the Readersmentioning
confidence: 99%